PENGARUH PENEGAKAN PERATURAN, KOMITMEN ORGANISASI, DAN GAYA KEPEMIMPINAN TERHADAP KECURANGAN (FRAUD) PADA SEKTOR PEMERINTAH (Studi Empiris Pada OPD Pemerintah Kabupaten Siak) - Randi, Randi; Basri, Yesi Mutia; Zarefar, Atika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study is to test the influence of (1) Regulation Enforcement, (2) OrganizationalCommitment, and (3) Leadership style on fraud in the government sector of the study in theSiak Regency OPD. In this study, the sample population was 43 regional apparatusorganizations. Sampling using Purposive Sampling. Data analysis used in this study wasusing multiple regression analysis techniques with a statistical approach operated throughthe SPSS program. The results of this study concluded that (1) Regulation Enforcement, (2)Organizational Commitment, and (3) Leadership style have an effect on fraud in thegovernment sectorKeywords: Fraud, Regulation Enforcement, Organizational Commitment, Leadership Style